2023
DOI: 10.22541/essoar.168988444.47343336/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ENSO and NAO Linkage to Strong Volcanism and Associated Post-Volcanic High-latitude Winter Warming

Abstract: High-latitude winter warming was observed following strong tropical volcanism, which has long been believed to be due to the volcanic-induced positive NAO phase. However, recent works argue that this warming is caused by ENSO variability. Moreover, controversies exist about the sensitivity of ENSO to volcanism. Therefore, to better resolve the controversies related to post-volcanic ENSO and NAO sensitivity and associated high-latitude winter warming, we conducted ENSO-preconditioned volcanic experiments using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Studies based on proxy reconstructions and climate models have shown that El Niño‐like conditions are common in the equatorial Pacific 0–2 years following explosive eruptions (Adams et al., 2003; Dogar et al., 2024; Emile‐Geay et al., 2008; Pausata et al., 2020; Stevenson et al., 2016; Tiger & Ummenhofer, 2023), although models may have a tendency to overestimate this effect (Dee et al., 2020). In CESM1, there is a much higher probability (up to 44%) of El Niño like SSTs in the equatorial Pacific in the second year following tropical eruptions and 1–2 years following northern eruptions (Table S1 in Supporting Information ), relative to non‐eruption years.…”
Section: Resultsmentioning
confidence: 99%
“…Studies based on proxy reconstructions and climate models have shown that El Niño‐like conditions are common in the equatorial Pacific 0–2 years following explosive eruptions (Adams et al., 2003; Dogar et al., 2024; Emile‐Geay et al., 2008; Pausata et al., 2020; Stevenson et al., 2016; Tiger & Ummenhofer, 2023), although models may have a tendency to overestimate this effect (Dee et al., 2020). In CESM1, there is a much higher probability (up to 44%) of El Niño like SSTs in the equatorial Pacific in the second year following tropical eruptions and 1–2 years following northern eruptions (Table S1 in Supporting Information ), relative to non‐eruption years.…”
Section: Resultsmentioning
confidence: 99%